Solving the Equation: 2n + 6 = 6
This article will guide you through the steps of solving the equation 2n + 6 = 6.
Understanding the Equation
The equation is a linear equation in one variable, 'n'. It means we need to find the value of 'n' that makes the equation true.
Solving for 'n'

Isolate the term with 'n': We need to get the term '2n' by itself on one side of the equation. To do this, subtract 6 from both sides: 2n + 6  6 = 6  6 2n = 0

Solve for 'n': Now, divide both sides by 2 to isolate 'n': 2n / 2 = 0 / 2 n = 0
Verification
To verify our solution, substitute 'n = 0' back into the original equation:
2(0) + 6 = 6 0 + 6 = 6 6 = 6
Since the equation holds true, we have confirmed that n = 0 is the correct solution.
Conclusion
Therefore, the solution to the equation 2n + 6 = 6 is n = 0.